Technology Blueprint Hello Meow Cat Shop / Syaidatul Umairah Solehah Abas - Abas, Syaidatul Umairah Solehah (2020)
The mission of the company is “To provide a complete package of products and services for every cat owner by offering the cat owners the best option of getting access to products that are organic treats which are free from any kind of preservatives, dyes, added sugar, sodium or fillers for example, 100% preservative free treats along with cat grooming services. All products will be developed with materials that are socially and environmentally friendly and the work environment will be conducive, rewarding and compatible with the requirements of the employees.”